Crenshaw - Applegate, Katherine (New York : Feiwel and Friends, 2015)
Jackson and his family have fallen on hard times. His parents, his little sister, and their dog may have to live in their minivan. Again. Crenshaw is a cat. He's large, he's outspoken, and he's imaginary. He has come back into Jackson's life to help him. But is an imaginary friend enough to save this family from losing everything?
Keywords: Poor families -- Juvenile fiction; Imaginary companions -- Juvenile fiction; Cats -- Juvenile fiction; Homeless persons -- Juvenile fiction